2017
DOI: 10.5152/tud.2017.93797
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and in vitro cultivation of human urine-derived cells: an alternative stem cell source

Abstract: Objective: For in vitro tissue engineering in urology, stem cells are commonly isolated from tissue specimens obtained during open or endoscopic surgery. Within the context of the present study our aim was to isolate cells from human urine by an alternative and safe technique rather than using the indicated method. Material and methods:After human urine samples had been collected from young and healthy donors via urethral catheterization, cells were precipitated by centrifugation and cultured. Following this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Those that were positive for CD90 were negative for CD45. This study demonstrated the presence of both cell types in fresh urine samples 14 .…”
Section: Resultssupporting
confidence: 60%
“…Those that were positive for CD90 were negative for CD45. This study demonstrated the presence of both cell types in fresh urine samples 14 .…”
Section: Resultssupporting
confidence: 60%
“…It has been reported that by collecting fresh urine samples, the success rate of isolating and cultivating human urine-derived cells (HUDCs) can be improved. However, UDSC viability can be lost if the time of exposure is greater than 5 h, as pH will start to change and nutrients in urine will be lost [32].…”
Section: Urine-derived Stem Cells (Udscs)mentioning
confidence: 99%
“…In a study conducted by Tayhan SE et al, it has been shown that urine-derived cells (UDCs) contain both stem cells as well as urothelial cells. As a maker of urothelial cells, cytokeratin 7 was used, whereas a negative and positive marker for mesenchymal stem cells of human, CD90, and CD45, respectively, were used [32]. ADSCs and UDSCs have shown a similar positive display of approximately more than 92% for CD73, and CD44 while ADSCs showed higher expression for CD105 and CD90.…”
Section: Markers Of Udscsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Studies showed that hUSCs had various biological characteristics of adult mesenchymal stem cells (MSCs) including clonogenicity, the expression of specific cell surface markers and multipotent differentiation ability. [1][2][3][4] HUSCs have been successfully isolated and continuous cultured in vitro in several laboratories. Because of a wide range of noninvasive sources and no ethical controversy, hUSCs have been induced to differentiate into various types of tissue cells such as osteoblasts, 5 chondrocytes, 6 adipocytes, 7 urothelial cells, 8 smooth muscle cells, 7 and nerve cells, 9 respectively.…”
Section: Introductionmentioning
confidence: 99%